TINJAUAN PENENTUAN PARAMETER KEKUATAN GESER TANAH DENGAN KORELASI HASIL UJI PENETRASI STANDAR (SPT) DAN BATAS-BATAS ATTERBERG DENGAN PENGUJIAN TRIAXIAL PADA TANAH DI BOYOLALI - Putra Perdana, I Gusti Putu Yoga; Purwana, Yusep Muslih; Setiawan, Bambang (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2021)
Soil investigations often encounter limitations that result in unavailability of the data required in calculation of building structure. These limitations can be in the form of geographical conditions, time of investigation, human resources, tools or budget availability. Researchers have previously studied the relationship between various soil parameters to determine other parameters required in civil building planning. In the railway construction project between Solo Balapan Station and Adie Soemarmo Airport Station, the engineering team conducted a fairly comprehensive soil investigation on the soil of Boyolali. This study studies the determination of the soil shear strength parameters using standard penetration test data and Atterberg limits test results in the project. The results of this determination are then compared with the available correlation formulas and graphs. The results showed that there was a significant difference between the correlation conducted by the researcher and the available correlation formulas and charts.